1ISG-020 Market access in the eu, do we have enough evidence? - Lluch, T Gómez (Eur J Hosp Pharm, 2018)
BACKGROUND: The European Medicines Agency (EMA) is responsible for the scientific evaluation of medicines for use in the European Union (EU), providing a scientific opinion on the granting of EU-wide marketing authorisations. PURPOSE: We conducted a retrospective analysis of new active substances (NAS) that had received positive opinion by the Committee for Medicinal Products for Human Use (CHMP) of the EMA, as well as the authorisation conditions and the findings of available therapeutic positioning reports (IPT) published in the Spanish Agency for Medicines and Health Products (AEMPS). MATERIAL AND METHODS: We analysed NAS with positive opinion from January 2014 until September 2017. We collected of each NAS the therapeutic area, the type of approval, the route used,, the designation obtained and pivotal trials (according to their design features using the European Public Assessment Reports) in order to evaluate the evidence provided. On the other hand, we verified the existence of IPT and analysed its conclusions, as well as the financing conditions. When an IPT included separate analyses for different indications, we included each separately. RESULTS: In this period, the CHMP approved the use of 132 NAS (41:2014, 39:2015, 27:2016, 25 until September 2017). Of these, 11% were conditional approvals (3:2014, 3:2015, 8:2016), and four exceptional, mainly in the cancer area. Moreover, 15% of approvals were carried out by accelerated routes due mostly also to the cancer area. Regarding the orphan designation, 32% were authorised under this (14:2014, 11:2015, 10:2016, 7:2017). Concerning the pivotal trials, 27% of NAS had at least one Phase-II trial between them. Of the 70 existing IPT, only 27% were classified as an advance in therapeutics. The majority were classified as similar to alternatives, considering its use based on efficiency criteria. Twenty-four per cent were not financed or under conditions by the AEMPS. CONCLUSION: The number of marketing approvals has been a continuing downward trend. However, authorisations with orphan designations and CMA have been increasing. This involved approval with early-stage clinical trials and lack of evidence. In order to avoid uncertainties in decision making, robust evidence must be available from the moment of authorisation to facilitate positioning. No conflict of interest